Victims of Cyber Extortion Among Kindergarten Students (Journal of the College of Basic Education, 2026)
This research aims to identify the prevalence of cyber extortion among kindergarten students and to reveal differences in the level of exposure to cyber extortion based on academic year (second year/fourth year). The research employed a descriptive-analytical approach and was conducted on a sample of 100 kindergarten students at the College of Basic Education, Al-Mustansiriya University. To achieve the research objectives, a standardized cyber extortion victimization scale consisting of 28 items was used. After verifying the instrument's validity and reliability, it was administered to the research sample, and the data were analyzed using appropriate statistical methods. The results showed a significant level of exposure to cyber extortion among kindergarten students. Furthermore, the results indicated statistically significant differences in the prevalence of cyber extortion based on academic year, favoring second-year students. In light of these findings, the research presents a set of conclusions and recommendations emphasizing the importance of enhancing digital literacy among students and organizing awareness programs within educational institutions to mitigate the phenomenon of cyber extortion.